Stimulate puppets’ law of motion in the natural relaxation An interview to puppet master and educator Mr. Tan Zhiyuan (Móin-Móin Magazine - Studies in the Art of Puppetry, 2018)
Interview Time: February 12, 2015, at 4PM -10PM. Interview Venue: Tan Zhiyuan’s home. Interviewed by Wang Xiaoxin (hereinafter, WANG), lecturer of Shanghai Theatre Academy Puppet Program, M.A. of Peking University, Special Research Fellow of Yale University Drama School. Interview to Tan Zhiyuan (hereinafter, TAN), Former Vice Chair of the China National Puppet Arts Troupe, First-grade Puppeteer, Member of Chinese Dramatists Association, Member of Council of China Puppetry and Shadow Arts Association.Rod puppet is an important form of Chinese puppet. Its structureand performing techniques are quite different from that of marionette andhand puppet. Rod puppet can be manipulated by a main-rod (connectedto a puppet head) and two hand rods (connected to puppet’s hands),known as "three rods", and it is named as "rod" for its resemblance to oldman’s walking stick. In China, the most representative rod puppet troupe is China National Puppet Arts Troupe2, in which Mr. Tan used to work.